An Interview with Jacob H. Rooksby, Dean of Gonzaga University School of Law - Zeller, Micah; Taylor, Tucker (Journal of Copyright in Education & Librarianship, 2018)
In this interview, Jacob Rooksby discusses his work and research in intellectual property and higher education law, including a critical examination of the role of copyright on the modern university campus. The conversation, with the Journal of Copyright in Education and Librarianship’s (JCEL) Micah Zeller and Tucker Taylor, covers trends concerning student entrepreneurship, faculty ownership, donor-imposed restrictions in special collections, and why everyone involved—from trustees, administrators, instructors, students, and library staff—should care and know how law and policies affect their interests. The discussion draws on Rooksby’s 2016 book, The Branding of the American Mind: How Universities Capture, Manage, and Monetize Intellectual Property and Why It Matters, which describes problematic practices of institutions, opportunities for those working in this space, and how intellectual property issues connect to our moral expectations for higher education. Professor Rooksby also flags areas for readers to keep an eye on in the future.